SUSTAINABLE BEEKEEPING IN ALGERIA: EXPLORING PRACTICES, CHALLENGES, AND LOCAL HONEYBEE TRAITS FOR NATURAL RESOURCE MANAGEMENT - Haider Yamina; Adjlane Noureddine; Martin-Hernande Raquel; Haddad Nizar; Abdelmounaim Khemmouli (Natural Resources and Sustainable Development)
Honeybees are crucial pollinators, playing a vital role in maintaining plant biodiversity and promoting a healthy natural environment. They serve as bioindicators, reflecting the state of our ecosystems. Beekeeping in Algeria faces significant challenges, particularly the devastating effects of the Varroa mite, an ectoparasite harming bee colonies. This study aimed at understanding the resilience of Mediterranean bee subspecies in the context of climate change. Conducted in 2021, a survey targeted Algerian beekeeping associations and individual beekeepers. The goal was to characterize beekeeping practices, identify key challenges, and evaluate their impact on natural resources and sustainable development. The survey reached beekeepers in 19 Algerian provinces, with a total of 200 responses analyzed. The results highlight constraints hindering beekeeping development: drought, high bee mortality, and the presence of bee diseases. These findings suggest that beekeepers who select colonies with strong overwintering and drought resistance capabilities can potentially improve honey production. The COVID-19 pandemic further impacted honey production, leading to lower yields in recent years. However, positive aspects were also identified, including beekeepers implementing good practices (queen replacement, apiary selection, transhumance) and routine Varroa mite monitoring. Strengthening the role of beekeeping associations in the field is crucial to support the sector's organization and improve its current situation, ultimately contributing to sustainable management of natural resources in Algeria.